Impact Of Population Growth and Poverty on Health in Nigeria - Oluwakemi Stella Olaniyan (IIARD INTERNATIONAL JOURNAL OF ECONOMICS AND BUSINESS MANAGEMENT, 2026)
The study examined the impact of population growth and poverty on health in Nigeria from 1981 to 2023. To achieve the objectives, annual time series data on Human Development Index (HDI), Population Growth Rate and Poverty were collected from secondary sources. The dependent variable was health which was proxy by life expectancy at birth. The independent variable – population growth (was disaggregated into rural and urban population growth rate) and poverty rate. The E-views 12 Statistical Software was employed to analyze the data empirically. The Unit root test was adopted to test the stationarity of variables. The Unit root test shows that Life expectancy at birth (LEB), Urban population growth rate (UPGR), and poverty rate (PVT) variables evaluated are all stationary after first difference I(1) while Rural population growth rate (RPGR) was stationary at level I(0). The result indicated that that the coefficients of UPGR, RPGR are positively signed and statistically significant in the long-run and short-run. It therefore means, UPGR and RPGR positively affect life expectancy at birth in Nigeria. The study recommends amongst others that the Nigerian government should raise minimum wage, create more employment opportunities, invest in quality and universal education, expand health and medical care, and provide easy access to the political process to reduce the poverty rate in the country.